PEMBUATAN GEL EKSTRAK DAUN PETAI CINA (Leucaena glauca, Benth) DENGAN BASIS GEL LIDAH (Aloe Vera L.) BUAYA SEBAGAI OBAT LUKA TERBUKA - Kurnia, Elvira Dita; Ratnasari, Dewi; Helmiawati, Yusi (Sekolah Tinggi Ilmu Kesehatan Holistik, 2019)
Background: Chinese Petai (Leucaena glauca, Benth) is a plant commonly used by the Cikampek community as a traditional wound medicine. Its use is traditionally chosen because it has no side effects to irritate the skin. However, it is impractical and cannot be stored for a long time, so there is a need for innovative, practical and durable preparations for storage. Objective: This study aims to determine how to make gel preparations from leaf extractsChinese petai leaf (Leucaena glauca, Benth) with base of Aloe Vera gel (Aloe Vera L.), and to know the stability of storage at room temperature. Method: This research method uses action research with research instruments in the form of literature studies and observation sheets. Two samples were prepared with the same composition, namely Chinese petai leaf extract (Leucaena glauca, Benth) 15 g and Aloe Vera L. 50 g. Results: The average percentage of yield shrinkage of Chinese petai leaf simplicia (Leucaena glauca, Benth) was 2,46%, Chinese petai leaf extract (Leucaena glauca, Benth) positively contained saponin based on the pH stability test decreased in storage, the gel dispersion obtained obtained met the criteria of 5 cm, homogeneous preparations, and last for 18 days.